Analysis of Risk Factors Affecting the Incident of Hypertension in Bawolato Health Center, Bawolato District, Nias District - Telaumbanua, Arman Budijaya; Amirah, Asriwati; Khairatunnisa, Khairatunnisa (Newinera Publisher, 2023)
Based on the 2021 Riskesdas results, the prevalence of the population with high blood pressure is 34.1%. Hypertension data from the Bawolato Community Health Center has increased over the last 2 years, with hypertension cases recorded in 2021 with a total of 842 cases and in 2022 with a total of 1,162 cases. Unhealthy lifestyles, with irregular eating patterns that lead to obesity, smoking, lack of physical activity and consuming too much alcohol, cause blood pressure to increase. The researcher's aim was to determine the risk factors that influence the incidence of hypertension at the Bawolato Community Health Center, Bawolato District, Nias Regency. This type of research is a case control survey. Case Control. The sample consisted of 104 respondents, 52 case groups and 52 control groups taken by consecutive sampling. Data analysis was carried out univariate, bivariate and multivariate using logistic regression tests. The results of the research on bivariate test analysis with chi-square showed that factors influencing the incidence of hypertension were obesity (p= 0.019; OR = 3.080), smoking (p= 0.037; OR= 2.182), physical activity (p= 0.006; OR= 1.875) , alcohol consumption (p= 0.029; OR= 3.407). Meanwhile, the multivariate test found that the factors that had the most influence on the incidence of hypertension were the alcohol consumption variable (p= 0.024; Exp(B)= 4.004) and the obesity variable (p= 0.006; Exp(B)= 3.857). It can be concluded that the risk factors for hypertension at the Bawolato Community Health Center, Bawolato District, Nias Regency are alcohol consumption and obesity. It is recommended that Puskesmas improve promotive and preventive services related to hypertension, educate the younger generation about the dangers of smoking and alcohol consumption, maintain diet, and exercise routine physical activity by utilizing the Health program as a bridge for education and health checks and collaborating with related sectors.